The combined effects of napping and self-selected motivation music during warming up on cognitive and physical performance of karate athletes - Bentouati, Emna; Romdhani, Mohamed; Abid, Rihab; Khemila, Syrine; Garbarino, Sergio; Souissi, Nizar (Frontiers in Physiology, 2023)
Introduction: It has been established that napping or listening to motivational music during warm-up is an effective strategy to enhance cognitive and physical performances. However, which could provide better enhancement warrants further investigation. This study aimed to examine the effect of a 30-min nap opportunity (N30), a warm-up with self-selected motivational music (WUMM), and the combination of N30 with WUMM (WUMM + N30) on cognitive and physical performances in karate athletes. Method: In a randomized order, 14 national-level male karate athletes performed four experimental sessions: control, N30, WUMM, and WUMM + N30. Simple (SRT) and choice (CRT) reaction times, selective attention, subjective sleepiness (ESS), mood state (POMS), countermovement jump (CMJ), and karate agility test (KAT) were evaluated before and after an all-out exhaustive task [i.e., the Karate Specific Test (KST)]. Ratings of perceived exertion (RPE) were measured immediately after the KST. Results: Compared to the control, all interventions improved cognitive outcomes, mood, and sleepiness. No effects on physical performances (CMJ and KAT) were found after N30. Compared to N30, WUMM + N30 improved SRT pre- and post-exercise (pre: p < 0.05, d = 0.72; post: p < 0.001, d = 0.14), CRT (pre: p < 0.001, d = 0.07; post: p < 0.001, d = 0.10), attention (pre: p < 0.05, d = 0.06; post: p < 0.01, d = 0.06), mood (pre: p < 0.001, d = 2.53; post: p < 0.001, d = 0.23), and decreased ESS scores (pre: p < 0.01, d = 1.41; post: p < 0.05, d = 1.18). However, there was no significant difference between WUMM and N30. KST performance was not affected by the experimental conditions. However, the KST-induced performance deficit in CMJ and KAT was smaller following WUMM + N30 compared to WUMM and N30. RPE scores were lower following WUMM + N30 and WUMM. Conclusion: These findings suggest that a combination of listening to self-selected motivational music during warm-up with a 30-min nap could be an effective strategy to enhance cognitive and physical performance decline caused by fatigue induced by exercise.